Psychosocial factors as mediator to food security status and academic performance among university students - Ahmad, Nor Syaza Sofiah; Sulaiman, Norhasmah; Sabri, Mohamad Fazli (MDPI, 2022)
The interrelation between food security, academic performance, and psychosocial factors remains unclear. This study aims to identify psychosocial factors as mediators of food security status and academic performance among university students at one of Malaysia’s public universities. Respondents included 663 bachelor’s degree students from seven randomly selected programmes at the university. Data on demographic and socioeconomic characteristics, food security status (US Adult Food Security Survey Module, FSSM), psychosocial factors (DASS-21), and academic performance were collected using an online survey. The SPSS PROCESS macro was used to perform mediation analysis. The result (β = −0.0182, p < 0.001) indicates that food insecurity is associated with poor academic performance. As well as that, an increase in anxiety (β = −0.0027, p < 0.05) and depression (β = −0.0025, p < 0.05) was significant associated with a decrease in academic performance. Furthermore, anxiety and depression serve as significant mediators in the relationship between food security and academic performance. Alleviating food insecurity is not only a way to improve academic performance; it can also improve academic performance by reducing anxiety and depression.